Green products purchase intention: a study of Sibu Sarawak - Wong, Jia Yii; Wong, Hui Shein; Wong, Winnie Poh Ming (Penerbit Universiti Kebangsaan Malaysia, 2020)
Of late, members of the public have become very concerned with both environmental issues and the role of the individual and their mindset towards keeping a healthy environment. The reason for this is because it has been identified that some of the main causes of environmental deterioration is due to the current rapid growth in technology and consumers’ consumption. The objective of this research is to identify the significant driver of green products purchase intention among residents of Sibu. Using the Theory of Reasoned Action as the underpinning basis, the study utilized a survey approach, with self-administered questionnaires. A total of 384 usable questionnaires were used for the purpose of analysis. The purposive sampling technique was used to distribute adapted questionnaires amongst the designated sample size. The results revealed that attitudes towards green purchase, health consciousness, attitudes towards the environment, and social influence led to consumers’ green products purchase intention.